2003
DOI: 10.1086/377706
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic Shock Heating of the Solar Corona

Abstract: Coronal MHD waves excited by perturbations of magnetic field lines propagate upward, carrying with them the energy from the excitation. Under favorable conditions shocks form, and part of the wave energy is converted to plasma heating and motion. We use numerical simulations to accurately follow the shock formation and subsequent energy release. The model includes an adiabatic energy equation for the explicit evaluation of temperature increases and energy fluxes contributed by the shocks. Transverse, plane-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Coronal heating and acceleration of the high-and low-speed solar wind in the open field region by dissipation of fast and slow MHD waves, through the formation of MHD shocks, was studied with 1D MHD models (Orta et al 2003;Suzuki 2004). Orta et al (2003) concluded that large amplitude MHD waves that steepen into fast and slow MHD shocks in low-beta regions could be a viable mechanism for coronal heating and wind acceleration in regions of open magnetic field lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronal heating and acceleration of the high-and low-speed solar wind in the open field region by dissipation of fast and slow MHD waves, through the formation of MHD shocks, was studied with 1D MHD models (Orta et al 2003;Suzuki 2004). Orta et al (2003) concluded that large amplitude MHD waves that steepen into fast and slow MHD shocks in low-beta regions could be a viable mechanism for coronal heating and wind acceleration in regions of open magnetic field lines.…”
Section: Discussionmentioning
confidence: 99%
“…Coronal heating and acceleration of the high-and low-speed solar wind in the open field region by dissipation of fast and slow MHD waves, through the formation of MHD shocks, was studied with 1D MHD models (Orta et al 2003;Suzuki 2004). Orta et al (2003) concluded that large amplitude MHD waves that steepen into fast and slow MHD shocks in low-beta regions could be a viable mechanism for coronal heating and wind acceleration in regions of open magnetic field lines. Similarly, Suzuki (2004) found that linearly polarised fast and slow magnetosonic waves traveling upwardly along the magnetic field eventually form fast switch-on shock trains and hydrodynamical shock trains, respectively, to heat and accelerate the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…In the solar atmosphere the formation and dissipation of shock waves has been studied in the context of heating the solar chromosphere (Orta, Huerta & Boynton 2003;Ulmschneider et Corresponding author: i.ballai@sheffield.ac.uk al. 2005) or acceleration of the solar wind (Cuntz & Suess 2004;Suzuki 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In analogy, all the action that drives coronal heating seems to come from upward-propagating waves at the footpoint of coronal loops or open field lines (Erdélyi 2004). The tickling stimulation can be arranged by a small-scale magnetic reconnection process or by magnetic flux emergence (Schmieder et al 2004a), while the signal propagates upward in the form of turbulence-driven Alfvén waves (Li & Habbal 2003;Dmitruk & Matthaeus 2003), ion-cyclotron waves (Markovskii & Hollweg 2004;Peter & Vocks 2003;Vocks & Mann 2004;, or fast-and slow-mode MHD shock waves (Orta et al 2003;Ryutova & Shine 2004;Cuntz 2004) generated by nonlinear Alfvén waves (Moriyasu et al 2004).…”
Section: Tickling Coronal Loops At Their Feetmentioning
confidence: 99%